Konseling Kelompok Solution Focused Brief Counseling (SFBC) untuk Meningkatkan Pemahaman Tupoksi Terhadap Perubahan Regulasi Kepegawaian di Institusi Pemerintah Daerah - Muhammad Hamdi; Affan Yusra; Freddi Sarman (Bulletin of Counseling and Psychotherapy, 2022)
The results of this study will be used in the Education Office of Muaro Jambi Regency. The importance of understanding the main duties and functions of regulatory changes because they are things that must even be carried out by a member of an organization or employee in an agency on a regular basis in accordance with their abilities to complete work programs that have been made based on the goals, vision, and mission of an organization. This study describes the group counseling solution focused brief counseling (sfbc) to improve understanding of the main duties and functions of changes in staffing regulations in local government institutions. This research is experimental research with The One Group Pretest-Posttest design. Analysis of the data in this study used the Wilcoxon test and there was an increase between the pretest and posttest. The results of this study indicate that the condition of the experimental group before being given treatment (Pretest) is in the medium category with a value of 102.4 then after being given treatment it increases with a value of 141.4 being in the high category. The Wilcoxon test results show that the use of the SFBT approach can improve understanding of the main tasks and functions of changing government regulations with a significance value of 0.002.